Efficient Energy Solution: Implementing a Smart PV-Generator Hybrid System for Enhanced Fuel Savings - Omar A. Abdulrazzaq; Aqiel Almamori; Raid K. Ibraheem; Sura N. Atewi; Haider S. Hussein (Tikrit Journal of Engineering Sciences)
The present study presents the design and implementation of a PV-generator hybrid system, integrating an on-grid PV system with a 0.5 MW diesel generator. The on-grid PV system, with a nominal power of 135 kW, was located on the top of the Renewable Energy and Environment Research Center building. The hybrid configuration serves as a reliable solution for power outages, seamlessly synchronizing the PV system with a microgrid formed by the generator. To ensure the robust operation of the system and prevent potential damage to the generator, an energy management system card was developed. This card incorporates a Reverse Power Protection Relay, programmed to disconnect one or two inverters, thereby limiting the PV penetration to below 75%. This measure guarantees a minimum generator load of 25%. The practical application of this setup demonstrated its effectiveness in powering building loads, resulting in a noticeable reduction in fuel consumption. The results indicate substantial fuel savings, with the generator demonstrating a 24-litre reduction in fuel gas per hour. This reduction equates to a cost savings of 8500 ID/h and a significant reduction of 50 kg/h in CO2 emissions. The inverter efficiency observed in this system ranged from 71% to 83%.